Assessment of Serum Zinc and Selenium Levels in Children with COVID-19 - Kirankaya, Aysegul; Ozel, Abdulrahman; Gayret, Ozlem Bostan; Atici, Adem; Tenekecigil, Aslihan; Erol, Meltem (Journal of Pediatric Infectious Diseases, 2022)
Objective Zinc and selenium levels are being investigated with increasing frequency in adult patients with coronavirus disease 2019 (COVID-19). However, levels of zinc and selenium in children with COVID-19 have not been adequately studied to date.Methods This prospective, observational study was conducted on 146 pediatric patients diagnosed with COVID-19 and 49 healthy controls between 2020 and 2021. Normal serum zinc reference values were 0.60 to 1.20 µg/mL for children 0 to 10 years old and 0.66 to 1.10 µg/mL for children ≥11 years old. The normal range for serum selenium concentration was considered between 70 and 150 µg/L. Deficiencies were defined for values below the reference range.Results Zinc and selenium levels were significantly lower in the COVID-19 (+) group compared with the controls (zinc: 0.7 ± 0.2 vs 0.9 ± 0.2 µg/mL, p < 0.001; selenium: 57.1 ± 9.1 vs 66.5 ± 11.4 µg/L, p < 0.01, respectively). Also, zinc and selenium levels were found to be statistically significantly lower in the hospitalized group compared with the outpatient group (zinc: 0.6 ± 0.2 vs 0.8 ± 0.2 µg/mL, p < 0.001; selenium: 52.1 ± 9.6 vs 58.8 ± 8.3 µg/L, p < 0.001). In the receiver operating characteristic curve analysis, selenium levels with a cutoff value of 55.50 µg/L, with 75% sensitivity and 70% specificity, and zinc levels with a cutoff value of 0.7 µg/mL, with 56% sensitivity and 53% specificity, predicted hospitalization.Conclusion Our data showed that serum zinc and selenium levels were significantly lower in patients with COVID-19 compared with healthy control group. Also, zinc and selenium levels were found to be lower in the hospitalized group compared with the outpatient COVID-19 group.
Keywords: zinc; selenium; COVID-19 in children